Unlocking markets and trade for rural development - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
The complexity of supply and demand and the nuances of trade and markets have grown exponentially as the world grows smaller. Fortunately, so have our tools to understand them and to harness the knowledge for pro-poor benefits.